Protection challenges of mobility - Phillips, M; Starup, K (Refugee Studies Centre, University of Oxford, 2014)
It is easy to say that people fleeing Syria should stay in camps or satellite cities but people move on for a variety of reasons, and programmes and services must adapt to assist them.